PENGARUH PEMAHAMAN PERATURAN PERPAJAKAN TERHADAP KEMAUAN MEMBAYAR PAJAK DENGAN SOSIALISASI PERPAJAKAN SEBAGAI ARIABEL MODERASI - Nova Sriani Siregar; Sri Lestari Hendrayati; Rini Oktavia (Balance: Media Informasi Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of understanding tax regulations on tax willingness with the socialization of taxation as a moderating variable in KPP Pratama Palangka Raya. The population taken in this study is the number of individual taxpayers registered at KPP Pratama Palangka Raya in 2019, which is 150,592. With a sample of 100 individual taxpayers who are determined by the Slovin formula. Then carried out the distribution of questionnaires using Google Forms (Google Form) through various social media in the city of Palangka Raya and the number of respondents obtained was 105 respondents. . Technique of data analysis tools used validity test by looking at Pearson Correlation and reliability test seeing Cronbach's Alpha value. Hypothesis testing techniques using partial test (t test) and Moderated Regression Analysis (MRA) test. Data processing in this study used the SPSS version 25 tool. The results showed that the influence of Tax Socialization as a Moderation Variable strengthens or increases the Understanding of Tax Regulations on the Willingness to Pay Taxes for Individual Taxpayers at KPP Pratama in Palangka Raya City